2023
DOI: 10.3390/heritage6070261
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Ecofriendly Mortars with Different Hemp Additions for Use in Building Sector

Daniel Ferrández,
Manuel Álvarez Dorado,
Alicia Zaragoza-Benzal
et al.

Abstract: Cement mortars are commonly used in building works for the execution of enclosures and exterior rehabilitation of facades. The incorporation of plant-based additives enables the development of ecofriendly construction materials. In this work, a physical and mechanical characterisation of cement mortars with the incorporation of hemp in three morphologies (fibre, powder and pellet) was conducted. The results show how the additions of hemp powder and pellets with a partial replacement of natural aggregate reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…This is attributed to the replacement of the original gypsum material with this plant-based addition, resulting in the composite retaining less water in its matrix. Similar observations have been made in prior research [11,58]. Additionally, it is observed that composites with hemp fiber addition exhibit a lower water absorption capacity compared to their counterparts with hemp powder.…”
Section: Tests On Behavior Regarding Water Exposuresupporting
confidence: 88%
See 1 more Smart Citation
“…This is attributed to the replacement of the original gypsum material with this plant-based addition, resulting in the composite retaining less water in its matrix. Similar observations have been made in prior research [11,58]. Additionally, it is observed that composites with hemp fiber addition exhibit a lower water absorption capacity compared to their counterparts with hemp powder.…”
Section: Tests On Behavior Regarding Water Exposuresupporting
confidence: 88%
“…In this work, we advocate for the use of hemp additions as a substitute for the original plaster material, aiming to develop environmentally friendly composites that are more cost-effective and meet regulatory requirements [11]. The basic components that impart properties to these natural fibers are cellulose, hemicellulose, and lignin [12].…”
Section: Introductionmentioning
confidence: 99%